The fibroblast growth factor‐23 and Vitamin D emerge as nontraditional risk factors and may affect cardiovascular risk. (29th March 2014) - Masson, S.; Agabiti, N.; Vago, T.; Miceli, M.; Mayer, F.; Letizia, T.; Wienhues‐Thelen, U.; Mureddu, G. F.; Davoli, M.; Boccanelli, A.; Latini, R.; The Investigators of the PREDICTOR study
Abstract Objectives Fibroblast growth factor‐23 (FGF‐23) and vitamin D are hormones involved in phosphate homoeostasis. They also directly influence cardiomyocyte hypertrophy. We examined whether the relationships between levels of vitamin D or FGF‐23, cardiac phenotype and outcome were independent of established cardiac biomarkers in a large cohort of community‐dwelling elderly subjects. Design and Setting Plasma levels of FGF‐23 and vitamin D were measured in 1851 men and women (65–84 years) resident in the Lazio region of Italy. Participants were referred to eight cardiology centres for clinical examination, electrocardiography, comprehensive Doppler echocardiography and blood sampling. All‐cause mortality or hospitalizations were available after a median follow‐up of 47 months with record linkage of administrative data. Results Vitamin D deficiency (<20 ng mL−1) was found in 72.3% of subjects, but FGF‐23 levels were normal [74 (58–97) RU per mL]. After adjustment for cardiovascular risk factors and morbidities, low concentrations of vitamin D and high levels of FGF‐23 were associated with a higher left ventricular (LV) mass index. Levels of FGF‐23 [hazard ratio (HR) (95% confidence interval (CI)) 1.71 (1.28–2.28), P < 0.0001] but not vitamin D [0.76 (0.57–1.01), P = 0.08] were independently associated with mortality after adjustment for clinical risk factors and two cardiac markers together (N‐terminal pro‐brain natriuretic peptide and high‐sensitivity cardiac troponin T), but did not predict hospital admission. People with above median values of FGF‐23 and below median values of vitamin D had greater LV hypertrophy and higher mortality. Conclusions In community‐dwelling elderly individuals with highly prevalent vitamin D deficiency, FGF‐23 levels were associated with LV hypertrophy and predicted mortality independently of two robust cardiac biomarkers. A causal relationship was not demonstrated, but the hormones involved in mineral metabolism emerged as nontraditional risk factors and may affect cardiovascular risk.